2018
DOI: 10.1371/journal.pntd.0006826
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices about human African trypanosomiasis and their implications in designing intervention strategies for Yei county, South Sudan

Abstract: BackgroundA clear understanding of the knowledge, attitudes and practices (KAP) of a particular community is necessary in order to improve control of human African trypanosomiasis (HAT).New screening and diagnostic tools and strategies were introduced into South Sudan, as part of integrated delivery of primary healthcare. Knowledge and awareness on HAT, its new/improved screening and diagnostic tools, the places and processes of getting a confirmatory diagnosis and treatment are crucial to the success of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…In general, the participants were aware and had good knowledge of sleeping sickness, its mode of transmission and the control strategy organized by the HAT national control program. Similar results have been previously described in South Sudan (Bukachi et al, 2018). Unlike in South Sudan where only 18% of participants reported sleep disorder, the majority of participants (91.6%) in the Bipindi focus reported that the latter is the most evocative sign of HAT.…”
Section: Discussionsupporting
confidence: 88%
“…In general, the participants were aware and had good knowledge of sleeping sickness, its mode of transmission and the control strategy organized by the HAT national control program. Similar results have been previously described in South Sudan (Bukachi et al, 2018). Unlike in South Sudan where only 18% of participants reported sleep disorder, the majority of participants (91.6%) in the Bipindi focus reported that the latter is the most evocative sign of HAT.…”
Section: Discussionsupporting
confidence: 88%
“…This observation is a positive one as females are more responsible in maintaining family hygiene and teach the children. The good knowledge, attitude and practice of female over male is supported by their lower mortality rate in this diseases, although female are globally more prone to this disease than male [32,42]. While the highest attitude score of the ‘Retired’ (7.55±0.69) was a reflection of their highest knowledge score; for other professional groups, knowledge scores mismatched their attitude scores.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the KAP model was developed for family planning and population studies in the 1950s, with its purpose being to measure the extent to which any clear opposition to the notion and organization of family planning existed among different populations, so specific family planning practices could be used for different program purposes worldwide [31]. KAP surveys are now the most widely used studies for uncovering societal context in public health research [32][33][34]. These surveys are easy to design, data output is quantifiable, interpretation is robust and their utility is generalizable for context specific problems [35].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…KAP was used to measure the extent to which any clear opposition to family planning existed among different populations, so specific family planning practices could be used for different programs worldwide [ 31 ]. KAP surveys are now the most widely used studies for demonstrating societal context in public health research [ 32 34 ]. These surveys are easy to design, data output is quantifiable, interpretation is robust, and their utility is generalizable for context-specific problems [ 35 ].…”
Section: Methodsmentioning
confidence: 99%